Conceptualizing student wellbeing in secondary education: a qualitative systematic literature review - Weiqi Jiang; Eisuke Saito; Hongzhi Zhang; Peter Waterhouse (International Journal of Adolescence and Youth)
A growing body of academic literature recognizes the importance of supporting students’ wellbeing in school settings. Approaches to supporting students’ wellbeing tend to focus on students’ subjective wellbeing, largely focusing on individuals’ mental health and advocating positive psychology. However, some studies have shown that socio-cultural factors, such as social equity, stigmas, and cultural norms also significantly impact students’ wellbeing. To build a holistic understanding of student wellbeing, this research constructs a comprehensive conceptual framework by systematically reviewing existing literature on students’ wellbeing within secondary education. It identifies factors such as health, autonomy, learning engagement, values, equity, and school culture as important attributes to students’ wellbeing. This review advocates for further research to explore the interaction among these factors, examining how educational pedagogies and practices can effectively nurture those factors without constraints.